ナンキョク ショウワ キチ タテモノ ノ プレファブリケーション システム ノ ヘンセン ニ ツイテ - 佐藤, 稔雄; サトウ, トシオ; 平山, 善吉; ヒラヤマ, ゼンキチ; Sato, Toshihiko; Hirayama, Zenkichi (1985)
P(論文) 現在, 南極昭和基地にある建物は4400m^2に達し, このうち約80%がいわゆるプレファブリケーションシステムによる建物である。ここでは, これらの建物の建設日数と延べ面積から建物別の施工速度と労務工数を求め, 著者らが設計上直面した課題と今までに試みた新提案に着目して, プレファブ化の意義や変遷をたどってみた。この結果, 基地の設営状況, 特に施工速度は日本国内に比べて群を抜いて早いことがわかった。 The total floor area of buildings at Syowa Station in Antarctica is 4400m^2 and about 80% of these buildings is prefabricated. This paper aims at reviewing the significance and the transition of prefabrication of buildings since the establishment of the station in 1957 with reference to the problems of design and the new proposals by the authors. To evaluate the superiority of prefabricated buildings, the construction speed and the labor were calculated on the basis of construction days and floor areas. departmental bulletin paper